Caries risk assessment: methods available to clinicians for caries detection - Tranæus S, Shi X-Q, Angmar-Ma°nsson B. (Blackwell Synergy, 2005)
It is hypothesized that occlusal lesions are initiated on the fissure walls and can therefore be obscured by sound superficial tissue.